Disleksia Metode Reading Aloud dalam Membantu Siswa dengan Kesulitan Belajar Disleksia: Pembelajaran inofatif progresif - Hendriyanto Bujangga Bujangga (PGMI IAIN Lhokseumawe, 2022)
In teaching learning process, there are several terms that have similar meanings, so people often feel confused to distinguish them. These terms are: (1) learning model (2) learning approach; (3) learning methods; (4) learning strategies; (5) learning techniques; and (6) learning tactics. Innovative progressive learning model is a form of learning that is illustrated from beginning to end which is presented specifically by the teacher. In other words, the learning model is a wrapper or frame from the application of an approach, method, and learning technique that introduces something new and brings about change towards improvement (for the better). As well as changing the paradigm of learning orientation which was originally teacher-centered (teacher center) to switch to student-centered (student center). The use of the Reading Aloud learning method is not only in language subjects but can be applied to other subjects according to the characteristics of the teaching material, the intended competence and the characteristics of the students. PAI learning which has the characteristics of the breadth of concepts and procedures with their application to students' lives requires the use of appropriate learning methods. For students with learning difficulties with dyslexia, PAI learning can be more effective and meaningful when using the Reading Aloud method. With Reading Aloud learning experience for both parties; teachers and students will get an atmosphere that supports students for the habit of reading, understanding reading and encouraging them to be more motivated to apply the teaching material they are learning.